Genome-wide identification and expression analysis of the Dof gene family under drought stress in tea (Camellia sinensis) - Yu,Qian; Li,Chen; Zhang,Jiucheng; Tian,Yueyue; Wang,Hanyue; Zhang,Yue; Zhang,Zhengqun; Xiang,Qinzeng; Han,Xiaoyang; Zhang,Lixia (PeerJ, 2020)
Background DNA-binding one zinc finger (Dof) proteins are plant-specific transcription factors important for seed development, hormone regulation, and defense against abiotic stress. Although drought stress is a key determinant of plant physiology and metabolic homeostasis, the role of Dof genes in different degrees of PEG6000-induced drought stress has received little attention. Methods Tea plants (Camellia sinensis) were exposed to mild, moderate and severe drought stress. The Tea Genome and Plant TFDB databases were used to identify Dof gene family members in the tea plant. Clustal W2.1, MEGA6.0, ScanProsite, SMART, ExPASy, GSDS, MEME and STRING were used to build a phylogenetic tree, predict the molecular masses and isoelectric points of the Dof proteins, and construct a predicted protein-protein interaction network between the CsDof TFs and proteins in the A. thaliana database. The expression patterns of Dof genes in different tissues were analyzed, and qRT-PCR was used to measure the expression of Dof genes under different degrees of drought stress in tea. Results We identified 16 Dof genes in tea (C. sinensis cv. Huangjinya) using whole-genome analysis. Through comparative analysis of tea and Arabidopsis thaliana, we divided the Dof genes into four families (A, B, C, and D). We identified 15 motifs in the amino acid sequences of the CsDof proteins. Gene sequences and motif structures were highly conserved among families, especially in the B1 and C2 subfamilies. The protein-protein interaction network indicated that multiple CsDof proteins may be involved in the response to drought stress. Real-time PCR was used to examine the tissue-specific expression patterns of the CsDof genes and to measure their responses to different levels of PEG6000-induced drought stress in mature leaves. Most CsDof genes responded to drought stress. These results provide information on the Dof gene family in tea, offer new insights into the function of CsDof genes in a perennial species, and lay the foundation for further analysis of their functions.
Keywords: Drought stress; Dof transcription factors; Gene expression; Tea